Bootstrap, jackknife and Edgeworth approximations for finite population L-statistics - Čiginas, Andrius (Lietuvos matematikos rinkinys, 2010)
In this paper we give exact bootstrap estimators for the parameters defining one-term Edgeworth expansion of distribution function of finite population L-statistic and compare these estimators with corresponding jackknife estimators. We also compare `````` true’ distribution of L-statistic with its normal approximation, Edgeworth expansion, empirical Edgeworth expansion and bootstrap approximation.
Keywords: finite population; sampling without replacement; L-statistic; Hoeffding decomposition; bootstrap; jackknife; Edgeworth expansion